Artists respond American art and the Vietnam War, 1965-1975 - Ho, Melisa; Crow, Thomas; Rosler, Martha; Nixon, Mignon; Levin, Erica; Markoski, Katherine; Minneapolis Institute of Art (Washington, DC Smithsonian American Art Museum, 2019)
"By the late 1960s, the United States was in a pitched conflict in Vietnam, against a foreign enemy, and at home--between Americans for and against the war and the status quo. This powerful book showcases how American artists responded to the war, spanning the period from Lyndon B. Johnson's fateful decision to deploy US Marines to South Vietnam in 1965 to the fall of Saigon ten years later. Artists Respond brings together works by many of the most visionary and provocative artists of the period, including Asco, Chris Burden, Judy Chicago, Corita Kent, Leon Golub, David Hammons, Yoko Ono, and Nancy Spero. It explores how the moral urgency of the Vietnam War galvanized American artists in unprecedented ways, challenging them to reimagine the purpose and uses of art and compelling them to become politically engaged on other fronts, such as feminism and civil rights. The book presents an era in which artists struggled to synthesize the turbulent times and participated in a process of free and open questioning inherent to American civic life. Illustrated in color throughout, Artists Respond features a broad range of art, including painting, sculpture, printmaking, performance and body art, installation, documentary cinema and photography, and conceptualism"--
One thing / Melissa Ho -- Chronology of events and Works in the exhibition / Melissa Ho and Katherine Markoski, with contributions by Robert Cozzolino, Joe Madura, Sarah Newman, and E. Carmen Ramos -- Bearing witness in American art of the Vietnam era / Thomas Crow -- To change the form of film / Erica Levin -- What's love got to do, got to do, with it? / Mignon Nixon -- Vietnam story / Martha Rosler.
"Published in conjunction with the exhibition of the same name, on view at the Smithsonian American Art Museum, Washington, DC, March 15, 2019 to August 18, 2019."
Includes bibliographical references and index.
Keywords: Art and war -- Exhibitions; Art, American -- 20th century -- Exhibitions; Art -- Political aspects -- History -- 20th century -- Exhibitions. -- United States; Art and society -- United States -- History -- 20th century -- Exhibitions